Polymorphism of The Mx Gene In Riau Kampung Chickens - Elfawati, Elfawati; Misrianti, Restu; Sadarman, Sadarman (Jurnal Ilmu Ternak Universitas Padjadjaran, 2026)
One of the genetic markers for avian influenza is the Mx gene. The purposed of this study was to determine the polymorphism of the Mx gene of kampung chicken in Riau Province. A total of 61 samples from three subpopulations have been genotyped using PCR-RFLP. Allele and genotype frequencies have been calculated using PopGene. The Mx gene was amplified, producing a DNA fragment measuring 299 base pairs. This fragment was digested with the Hpy81 enzyme, which yielded three genotypes: the AA genotype showed by a single 299 bp band; AG showed by 299, 200, and 99 bp bands; and GG genotyped showed by  200 and 99 bp bands. AA Genotype frequency is higher than the AG and GG genotypes in Indragiri Hulu and Kampar. the A allele frequency is higher than the G in two populations, i.e., Kampar at 78% and Indragiri Hulu at 70%. Kuantan Singingi have the highest value for Heterozygosity observation. This study concludes that the Mx gene in kampung chicken Riau Province was polymorphic. There are three genotypes of Mx│Hpy81 gene that is AA, AG, and GG and two alleles that is A and G. Observed heterozygosity value showed that the genetic diversity in Kampar and Indragiri Hulu subpopulation is low